2020
DOI: 10.1371/journal.pone.0238989
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age on goal-framing for health messages: The mediating effect of interest in health and emotion regulation

Abstract: Messages to promote health behavior are essential when considering health promotion, disease prevention, and healthy life expectancy. The present study aimed to examine whether (1) positive and negative goal-framing messages affect message memory and behavioral intention differently in younger, middle-aged, and older adults, (2) framing effects are mediated by interest in health (health promotion and disease prevention) and emotion regulation (cognitive reappraisal and expressive suppression), and (3) mediatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…In bivariate analysis, age under 55 was associated with pre-hospital delay, but this association was not significant in multivariate analysis.This finding is consistent with the study results of Masumoto et al [ 76 ], which showed that older participants appeared more interested in their health than younger participants.…”
Section: Discussionsupporting
confidence: 93%
“…In bivariate analysis, age under 55 was associated with pre-hospital delay, but this association was not significant in multivariate analysis.This finding is consistent with the study results of Masumoto et al [ 76 ], which showed that older participants appeared more interested in their health than younger participants.…”
Section: Discussionsupporting
confidence: 93%
“…This was supportive of the high GHI of the middle-aged group. A previous study [64] also mentioned that older participants were more interested in health. In addition, Cronbach's alpha for the internal reliability of each factor was similar to the previous research [37] result of 0.89, as the values were 0.83 for the youth group and 0.82 for the middle-aged group.…”
Section: General Health Interest (Ghi)mentioning
confidence: 93%
“…Regarding goal-framing, only one study to date has examined the effect of age in adults' susceptibility to this type of framing. Masumoto et al (2020) demonstrated that younger adults were less susceptible to the framing effect when presented with the positive frame, and vice versa. Similarly, Sparks and Ledgerwood (2018) conducted the sole study addressing the effect of age on the attribute framing effect.…”
Section: Introductionmentioning
confidence: 95%